Torque Smoothing of a Fault Tolerant Segmental Stator Switched Reluctance Motor - Szabo, Lorand; Ruba, Mircea; Fodorean, Daniel; Rafajdus, Pavol; Dubravka, Peter (Communications - Scientific Letters of the University of Zilina, 2015)
The relatively high torque ripples are one of the main disadvantages of the switched reluctance motors. By smoothing their torque they can become more competitive for variable speed drives used in automotive and industrial applications. One of the most promising approaches to reduce the torque ripples of a SRM is the use of a direct instantaneous torque controller. In the paper the effectiveness of this type of control will be proved for a fault tolerant segmental stator SRM. By advanced simulation techniques the working principle of the direct instantaneous torque controlled drive system is illustrated, and its performances are demonstrated.
Keywords: switched reluctance motor; segmental stator construction; direct instantaneous torque control; simulation